2022
DOI: 10.3755/galaxea.g2021_s14o
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends and seasonal variations in environmental conditions in Sesoko Island, Okinawa, Japan

Abstract: Knowledge of environmental factors is crucial in understanding biological and ecological processes. Yet information on the environment around Sesoko Island, Okinawa, Japan, one of the main locations for coral reef research in Japan, remains scarce. Data of air and sea surface temperature (SST), wind velocity, wave height, and frequency of typhoons have been manually recorded at Sesoko Station, Tropical Biosphere Research Station, the University of the Ryukyus from September 1990 to November 2021. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…No information is available on upwelling around Okinawa during the coral reproductive season. However, at the time of larval release, typhoons could create enough vertical water movement to potentially transport S. hystrix larvae from mesophotic depths to shallow reefs, although the frequency and paths of strong storms vary across years 9 , 33 . This stochastic connectivity may explain the absence of genetic partitioning within the water column for S. hystrix in Okinawa 26 .…”
Section: Discussionmentioning
confidence: 99%
“…No information is available on upwelling around Okinawa during the coral reproductive season. However, at the time of larval release, typhoons could create enough vertical water movement to potentially transport S. hystrix larvae from mesophotic depths to shallow reefs, although the frequency and paths of strong storms vary across years 9 , 33 . This stochastic connectivity may explain the absence of genetic partitioning within the water column for S. hystrix in Okinawa 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides temperature, several environmental factors such as lower light intensity, higher wind speed, higher water flow, and typhoons can also mitigate coral bleaching severity ( Fitt & Warner, 1995 ; Nakamura & van Woesik, 2001 ; Smith, 2001 ; West & Salm, 2003 ). However, in our study, the light and precipitation regime, wind speed, wave height, number of cloudy days, and the timing and frequency of typhoons around the study site were found to be similar in the summer of 2016 and 2017 (Table S4; Supplemental Data in Singh et al, 2022 ). This indicates that the improved heat-stress tolerance was not caused by adaptation or better environmental conditions in 2017, but by the acclimatization of the coral holobionts.…”
Section: Discussionmentioning
confidence: 53%
“…For example, failure to acclimatize to a simulated consecutive bleaching event was linked to low basal energy reserves, which in turn was attributed to the peak in temperatures coinciding with end of the reproductive season ( Grottoli et al, 2014 ; Schoepf et al, 2015 ). Acropora corals at our study site generally spawn synchronously in June, a month before the temperatures begin to rise ( Baird et al, 2022 ; Singh et al, 2022 ). Although we do not know if this is enough time for Acropora corals to recover their basal energy reserves after reproduction, the reproductive period does not overlap with increased heat stress at our study site.…”
Section: Discussionmentioning
confidence: 99%
“…Okinawa’s south-to-north ubanization gradient sets up a unique natural laboratory to investigate the ecological outcomes from intense urbanization of a subtropical island and creates the opportunity to fill a critical knowledge gap as islands across tropical and subtropical regions are experiencing increasing tourism demand, growing populations, and accelerating urbanization (Bertolo et al 2012; Lin et al 2013). Okinawa also has a strong land-sea connection due to frequent and intense rain events associated with a spring monsoon season and a summer/fall typhoon season (Singh et al 2022). Okinawa is located in typhoon alley, the most active region for tropical cyclones on Earth (Magee et al 2021).…”
Section: Introductionmentioning
confidence: 99%